Optimal time-domain technique for pulse width modulation in power electronics - I. Mayergoyz; S. Tyagi (AIP Advances, 2018)
Optimal time-domain technique for pulse width modulation is presented. It is based on exact and explicit analytical solutions for inverter circuits, obtained for any sequence of input voltage rectangular pulses. Two optimal criteria are discussed and illustrated by numerical examples.